2009
DOI: 10.1128/jvi.00232-09
|View full text |Cite
|
Sign up to set email alerts
|

Dimerization and a Novel Tax Speckled Structure Localization Signal Are Required for Tax Nuclear Localization

Abstract: The human T-cell leukemia virus type 1 oncoprotein Tax has pleiotropic activities, a subset of which likely leads to immortalization of T cells. Tax is expressed and known to function in both the cell nucleus and the cytoplasm. Tax has defined nuclear localization (NLS) and nuclear export signals that enable shuttling between the two compartments. In this study, we identified a novel region in Tax that targets the protein to discrete nuclear foci that we have previously termed Tax speckled structures (TSS). We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 72 publications
0
17
0
Order By: Relevance
“…Importantly, this 2 to 22 deletion does not affect the zinc finger motif of Tax, required for its nuclear localization. 20,21 Tax was able to associate with endogenous members of the MCM2-7 complex but failed to bind other replication regulators, such as MCM10 or HBO1 ( Figure 1B; and data not shown). The physiologic relevance of the interaction between Tax and endogenous MCM3 was further validated in HTLV-1-infected cell lines ( Figure 1C).…”
mentioning
confidence: 99%
“…Importantly, this 2 to 22 deletion does not affect the zinc finger motif of Tax, required for its nuclear localization. 20,21 Tax was able to associate with endogenous members of the MCM2-7 complex but failed to bind other replication regulators, such as MCM10 or HBO1 ( Figure 1B; and data not shown). The physiologic relevance of the interaction between Tax and endogenous MCM3 was further validated in HTLV-1-infected cell lines ( Figure 1C).…”
mentioning
confidence: 99%
“…Specific sequences within Tax that serve to signal nuclear localization, 6 nuclear export, 5,8 specific targeting to TSS's, 7 and cellular secretory activity have been identified. 42 It is also clear that posttranslational modification of Tax provides a rapid way to regulate subcellular localization, possibly via modification of the presentation of these defined localization signals.…”
Section: Discussionmentioning
confidence: 99%
“…The Tax protein contains a nuclear localization signal, 6 and we recently identified a specific signal sequence that targets Tax to nuclear bodies. 7 We and others have described a nuclear export signal. 5,8 In addition, Lamsoul et al showed that ubiquitylation of Tax is correlated with its accumulation in the cytoplasm, whereas sumoylation of Tax is required for nuclear localization.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Many studies have shown that sumoylation, ubiquitination, acetylation, and phosphorylation play a critical role in the subcellular localization, protein–protein interaction and function of both Tax-1 and Tax-2, revealing similarities and differences between the two transactivators (Bex et al, 1999; Chiari et al, 2004; Lamsoul et al, 2005; Durkin et al, 2006; Nasr et al, 2006; Gatza et al, 2007; Lodewick et al, 2009; Turci et al, 2009; Bidoia et al, 2010; Bertazzoni et al, 2011; Journo et al, 2013). In addition, dimerization of Tax-1 is necessary for its nuclear localization and interaction with CREB and the 21-bp repeat elements (Tie et al, 1996; Jin and Jeang, 1997; Basbous et al, 2003; Fryrear et al, 2009). Similarly, we previously described that CIITA expressed in cells, but not CIITA produced in vitro , forms homodimers in a phosphorylation-dependent manner (Tosi et al, 2002) and this modification is a prerequisite to CIITA nuclear retention (Tosi et al, 2011).…”
Section: Ciita Targets Tax-1 and Tax-2 Transactivators To Inhibit Virmentioning
confidence: 99%